Kinerja Usaha Berbasis Orientasi Kewirausahaan, Kapabilitas Jejaring Wirausaha dan Komitmen Organisasi - Silaningsih, Endang; Haryadi, Mohammad Mursidi; Yuningsih, Erni (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Siliwangi, 2025)
This study aims to determine the effect of entrepreneurial orientation, entrepreneurial networking capabilities and organizational commitment on the performance of snack food MSMEs in West Bogor district. The population in this study were snack food MSMEs in West Bogor district amounted to 1,540 with a sample of 100 and data analysis using descriptive and verification methods with multiple linear regression analysis through the IBM SPSS program version 25.00. The results of the study indicate that entrepreneurial orientation, entrepreneurial networking capabilities and organizational commitment have a positive and significant effect both simultaneously and partially on business performance. The resulting impact is that MSMEs have a strong entrepreneurial spirit, are able to build extensive networks, and have a high commitment to their business, so their business performance will increase significantly in terms of sales, growth, innovation, and competitiveness.